Lipothymic episode in a diabetic military pilot: diagnostic pathway and flight fitness management - Palumbo, Fabrizio; Marfia, Giovanni; Navone, Stefania E; Garzia, Emanuele; Bignami, Fabio; Ciniglio Appiani, Giuseppe (La Medicina del Lavoro, 2020)
We report a case study of a military helicopter pilot, 56-year-old with a lipothymic episode during a mission in Afghanistan. He had increased cardio and cerebrovascular risk factors, suffering from type II diabetes mellitus under diet therapy. The management of the clinical case consisted basically of 2 phases: acute management in an advanced field hospital which excluded the presence of cerebral ischemic events and assessment of the fitness to fly. In Italy second-level investigations of neuroradiological relevance were carried out which excluded changes in the flow of the intra and extra-cranial circulation, highlighting more of an initial damage to the microcirculation with findings compatible with chronic microvasculopathy. A cardiologic evaluation was also carried out without signs of ischemic heart disease. Nevertheless, the patient presented also a metabolic syndrome so a complete medical evaluation had to be performed to assess the fitness to fly according to the current standards for flying safety.